METODE BIMBINGAN KONSELING DALAM PEMBINAAN AKHLAK SISWA DI MADRASAH ALIYAH (Fakultas Dakwah dan Komunikasi, 2020)
The study uses a qualitative research type with a guidance approach and a psychological approach. The primary data source is Ir. Subhan as a counseling teacher, additional informant is the school principal, guardian, and teacher and the students. Secondary data sources are books, journals, and other writings that can be used as complementary data. As well as analysis of data carried out with three stages of data reduction, data presentation, and withdrawal of conclusions. The results of the study showed that the teacher's efforts in the development of students were individual tutoring, group guidance, the method of moral, religious aggression and punishment. Supporting factors in the development of students, namely the collaboration of teacher counseling teachers with teachers, counseling teachers' cooperation with parents, and learners with teachers. The termination factor is the absence of a schedule of permanent guidance, lack of competence of the BK teachers, as well as the discipline of students.